1997
DOI: 10.1161/01.cir.96.7.2162
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction and Cardiac Mortality in the Bypass Angioplasty Revascularization Investigation (BARI) Randomized Trial

Abstract: The Bypass Angioplasty Revascularization Investigation (BARI) trial indicates 5-year cardiac mortality in patients with multivessel disease was significantly greater after initial treatment with PTCA than with CABG. The difference was manifest in diabetic patients on drug therapy. There were no significant differences overall for the composite end point of cardiac mortality or MI between treatment groups or for cardiac mortality in nondiabetic patients regardless of symptoms, left ventricular function, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 28 publications
1
41
0
5
Order By: Relevance
“…two or more years after index admission) mortality for patients receiving CABG versus PTCA. For example, the Bypass Angioplasty Revascularization Investigation (BARI) trial found that, for non-diabetic patients with multivessel disease, there was no significant difference in the 5-year mortality for patients randomized to either CABG or PTCA (Chaitman et al, 1997). For multivessel patients with diabetes, those receiving CABG had significantly lower 5-year mortality than those receiving PTCA.…”
Section: Treatment Substitutionmentioning
confidence: 99%
“…two or more years after index admission) mortality for patients receiving CABG versus PTCA. For example, the Bypass Angioplasty Revascularization Investigation (BARI) trial found that, for non-diabetic patients with multivessel disease, there was no significant difference in the 5-year mortality for patients randomized to either CABG or PTCA (Chaitman et al, 1997). For multivessel patients with diabetes, those receiving CABG had significantly lower 5-year mortality than those receiving PTCA.…”
Section: Treatment Substitutionmentioning
confidence: 99%
“…For this analysis, the criteria used for diagnosing MI in hospital and during follow-up were similar to the MI definition used for BARI. 11 In the 96 hours after the revascularization procedure, MI was defined as the presence of a new Q wave on the postprocedural ECG; after the 96 hours, Q-wave and non-Q-wave MIs (identified on the basis of enzymes, chest pain, or ECG changes) were counted. Definitions of other end points have been described previously.…”
Section: Definitionsmentioning
confidence: 99%
“…12 As the applicability of PCI expanded, randomised data showed that surgical and percutaneous revascularisation were equivalent in terms of both survival and future risk of MI. 13 The latter strategy, however, would incorporate a greater likelihood of requiring a further intervention because of restenosis, but the introduction of routine stenting 14 -particularly with drug-eluting devices 15 -soon eroded this difference.…”
Section: The Evidence Basementioning
confidence: 99%